Enabling actors' viable behaviour: reflections upon the link between viability and complexity within smart service system. (2018) - Polese, Francesco; Carrubbo, Luca; Bruni, Roberto; Caputo, Francesco
Over time an increasing attention has been paid to the concept of complexity but a clear definition of their implication and useful guidelines to manage its dynamics seem to be still missing in managerial studies. With the aim to bridge this gap, the paper aims to link the conceptual framework provided by the systems thinking (ST) and service science (SS). The attention is focused on the role of viability in supporting a better understanding and managing of internal and external complexity with specific reference to the domain of smart service systems (SSS). Building upon a multi-disciplinary conceptual framework, the paper traces some reflections to address decision makers' strategies and behaviours in managing SSS with the aim to increase opportunity for survival through a better understanding of logics and dynamics of complexity.